Peningkatan Kinerja Guru Kelas IV Dalam Menetapkan Kriteria Ketuntasan Minimal Melalui KKG di Gugus II Kecamatan Sumobito - yayuk, yayuk (Universitas Negeri Surabaya, 2020)
In setting the KKM (inimal submission criteria), the teacher has not been based on analysis and has not noticed the principles and determination measures. Therefore, there must be activities that can provide information to teachers who are used as guidelines in the determination of the KKM. The purpose of this research is to increase the ability of class IV teachers to set the KKM through group of teacher (KKG) in cluster II in Sumobito subdistrict. The subject of this research is the teacher at SDN class IV cluster II Sumobito subdistrict. The research object is the ability of teachers to establish Minimal submission criteria. Based on the analysis it gained that there was increased readiness and performance of the teacher in setting the minimum survival criteria from cycle I to cycle II. The achievement of performance indicators is in action II. In addition, there has been an increase in the teacher's ability to set Minimal submission criteria through a KKG-shaped coaching from cycle I to cycle II and achieve a set minimum target of 85%, meaning that 85% of teachers are effective in establishing Minimal submission criteria. Thus it can be advised to other supervisors or researchers that the KKG activities can be used as an alternative in improving the performance of teachers in setting the minimum submission criteria.